Central African Republic : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Central African Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Staff Report for the 2011 Article IV Consultation found the macroeconomic performance of the Central African Republic (CAR) satisfactory despite its below-average growth compared with other countries of the region. The report has identified lack of resources, institutional frailties, overdependence on external assistance among other factors responsible for the tardy economic growth and increase in poverty. However, the report has observed that the economy is poised for a medium-term recovery with budgetary discipline and transparency, and effective management of public debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet